2015
DOI: 10.5771/0935-9915-2015-2-123
|View full text |Cite
|
Sign up to set email alerts
|

Job design, work engagement and innovative work behavior: A multi-level study on Karasek’s learning hypothesis

Abstract: As employees' behaviour is a crucial factor for organizational success, the question on how to promote the engagement of employees in their work and boost their implication in the innovation process is central for companies. In this article we study this question building on the Karasek model suggesting that employees in jobs with high autonomy and time pressure will be more engaged and more innovative. The results of the multi-level regression analyses confirm that such a combination is associated with high e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…Alpkan et al (2007) also indicated that work discretion, which is an ability to take initiative in decision-making, enhances innovativeness and overall performance. Work discretion, which is also known as autonomy in the workplace, is a strong indicator for revealing innovative behaviors among employees (De Spiegelaere, Gyes, De Witte, Niesen, & Van Hootegem, 2015). Similar findings were found by Dess et al (2003) whereby the study provided evidence of a strong relationship between work discretion and entrepreneurial orientation.…”
Section: Discussionsupporting
confidence: 77%
“…Alpkan et al (2007) also indicated that work discretion, which is an ability to take initiative in decision-making, enhances innovativeness and overall performance. Work discretion, which is also known as autonomy in the workplace, is a strong indicator for revealing innovative behaviors among employees (De Spiegelaere, Gyes, De Witte, Niesen, & Van Hootegem, 2015). Similar findings were found by Dess et al (2003) whereby the study provided evidence of a strong relationship between work discretion and entrepreneurial orientation.…”
Section: Discussionsupporting
confidence: 77%
“…Work method autonomy gives employees the necessary space to experiment with alternative work procedures and methods, innovations they can propose at a later stage. Various empirical studies have confirmed this positive effect of work method autonomy on employee innovative behavior (De Spiegelaere, Van Gyes, De Witte, & Van Hootegem, ; Molleman & van den Beukel, ; Rodríguez, Buyens, Van Landeghem, & Lasio, ; Shalley & Gilson, ). We consequently hypothesize that work methods autonomy will be positively related to IWB and work engagement.…”
Section: The Impact Of Job Autonomy On Work Engagement and Iwbmentioning
confidence: 82%
“…The Finnish sample of this study is in many ways typical of the modern knowledge worker: highly educated, facing high challenge demands at work, but at the same time also enjoying high decision latitude to organize demanding work. According to the job demands-control model, this combination results in 'active jobs', which are related to high motivation and well-being in employees (Karasek, 1979;Karasek & Theorell, 1990) and may therefore result in high job performance such as innovative work performance (De Spiegelaere, Van Gyes, De Witte, & Van Hootegem, 2015).…”
Section: Discussionmentioning
confidence: 99%